Grass [videorecording (DVD)] - Kim, Min-hŭi, 1982-; Kee, Joobong; An, Chae-hong, 1986- (Cinema Guild, 2020)
In the corner of a small cafe, Areum sits typing on her laptop. At the tables around her, other customers enact the various dramas of their lives. Is she merely writing what she hears? Or is she hearing what's been written? As dramas inside the cafe unfold, the plants outside grow taller.